STUDIES ON SUN FLOWER OIL [Helianthus annuus Linn] FOR ITS POTENTIAL USE AS BIODIESEL - VN, Ariharan; Vn, Meena Devi; NK, Parameswaran; P, Nagendra Prasad (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Biodiesel is gaining more and more importance as an attractive fuel due to the depleting fossil fuel resources. The Sun flower is valuable from an economic, as well as an ornamental plant. It is one of the important oil seed crop, cultivated for the production of oil in the world especially from western countries. Sun flower seed oil is a triglyceride derived from the seeds of the Sun flower. It belongs to the family Asteraceae. The oil can be used for cooking and the seeds also food for birds. In this study the seeds were collected from the local market and oil was obtained by using chemical extraction. Sun flower oil was subjected to various physical and chemical studies such as pH, Specific gravity Density and Viscosity. The Fire points, Flashpoint, Cloud point, Pour point, Carbon residue. The chemical properties like Acid value, Iodine value, and saponification value were assessed. The Physico- Chemical Properties of the Sun flower oil biodiesel blends 10% (B10) and 20% (B20) were analyzed. The values were compared with the ASTMT standards of biodiesel. The blend B20 is found to be within the ASTM standard and it could be used as alternative energy source as biodiesel.